Visionary Eschatology: Piers Plowman - Aers, David (Modern theology, 2000)
In its later versions Piers Plowman is a long, complex poem of extraordinary formal, theological, and political complexity. It is one of the greatest Christian poems. Written in a period of unprecedented conflict in English polities, including the Church, it was passionately involved in exploring many of these conflicts while seeking to imagine projects of Reformation. The poem includes fascinating reflections on diverse eschatological traditions within the late medieval Church, including neo-Joachite ones. Subjecting both the contemporary Church and such eschatologies to sustained critique, the author evolves a profoundly Christocentric vision in the light of which triumphant narratives of the Church would emerge as among the opiates threatening the Church at the poem's close.